Evidence for IL-35 Expression in Diffuse Large B-Cell Lymphoma and Impact on the Patient's Prognosis - Larousserie, Frédérique; Kebe, Diakho; Huynh, Tony; Audebourg, Anne; Tamburini, Jérôme; Terris, Benoît; Devergne, Odile (Frontiers in Oncology, 2019)
IL-35 is an immunosuppressive cytokine of the IL-12 family consisting of two subunits, EBV-induced gene 3 (EBI3) and p35. It has been shown to play a pro-tumor role in murine tumor models, and in various types of human cancer such as colorectal, pancreatic, or liver carcinoma, its expression has been associated with a worse clinical outcome. Here, we show by analyzing gene expression data from public databases and by immunohistochemical studies that IL-35 is overexpressed by tumor cells in diffuse-large B-cell lymphoma (DLBCL) compared to another type of mature aggressive B-cell lymphoma, Burkitt lymphoma. However, while high IL-35 expression was significantly associated with a worse overall survival in DLBCL patients treated with chemotherapy only (cyclophosphamide, doxorubicin, vincristine, prednisone, CHOP), no significant correlation between IL-35 expression levels and the patient outcome was observed in DLBCL patients treated with CHOP combined to rituximab (R-CHOP), the current conventional treatment. In addition, we found that an anti-IL-35 antibody, clone 15k8D10, used to assess IL-35 expression by immunohistochemistry in various human tissues including tumors does not recognize IL-35 heterodimer, nor its individual subunits EBI3 and p35, but cross-reacts with human IgG1, indicating that IL-35 expression in human cancers needs to be re-evaluated.